EFFECT OF CRUED EXTRACTS FOR CINNAMUM (Cinnamum zeylaicum), SYZYGIUM (Syzygium aromaticum) AND THYMUS (Thymus vulgaris) ON GROWTH OF Aspergillus flavus WHICH PRODUCE AFLATOXIN B1 - Al-saidy, Hadi Alwan; Al-qrtani, Yaser M.; Al-Zubaidy, Najm Abdullah (Diyala Agricultural Sciences Journal, 2013)
This study was carried at College of Education for Pure Science – Diyala university during 15-3-2011 to 20-6-2012, it had been used plant extracts of Cinnamon (Cinnamon zylanicum), Syzygium (Syzygium aromaticum) and Thymus (Thymus vulgaris).Four different methods of extraction to test their efficacy to inhibit growth of Aspergillus flavus which produces aflatoxin B1, Results of this study showed that the activity of plant extracts For Cinnamum, Syzygium and Thymus against Aspergillus flavus Which produced aflatoxin B1, Hexanes extract for Cinnamum and Syzygium and Thymus achieved a higher percentage of inhibition 100% at 110, 250 and 250 µg/ml. Also alcoholic extracts inhibited A. flavus at 220 , 500 and1000 µgwith 100% inhibition percentage ,Cold water extracts at 1250 , 850 , 1250 µgconcentration gave a higher percentage of inhibition 100% , Hot water extracts at 1300 ,1100 and1350 µgconcentrations respectively (Cinnamum , Syzygium , Thymus) gave percentage of inhibition 100% . Also the results showed that the hexanes extracts for Cinnamum, Syzygium and Thymus were the best extracts in inhibition growth of A. flavus which produces aflatoxin B1 when they compared with other extracts. The average of inhibition concentrations to A. flavus from hexanes extracts was 203 µg, and the average of inhibition concentrations of growth A. flavus from hexanes extracts was 166 µgwith inhibiting percentage 57% while the average of inhibition concentrations to A. flavus from alcoholics extracts was 573 µg,So the average of inhibition concentrations of growth A. flavus from alcoholics extracts was 360 µgwith inhibiting percentage 47.8% , The average of inhibition concentrations to A. flavus from cold water extracts was 1116.6 µg,and the average of inhibition concentrations of growth A. flavus from cold water extracts was 933 µgwith inhibiting percentage 60% .at last hot water extracts the average of their inhibition concentration to A. flavus was 1250 µgand average of inhibition concentrations of growth A. flavus was 1166.6 µgwith inhibiting percentage 52.84% .So the results showed most active antifungal against A. flavus at 100 µgconcentration with inhibiting percentage 100% was Ketocanazol when it comparison with a highest inhibiting percentage for antifungal Flucanazol in which was 37.8% against A. flavus at 100 µgconcentration.